2019
DOI: 10.3390/nu11051116
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum Extract Reduces the Motility of Breast Cancer Cells Mediated by the RAC–Lamellipodin Axis

Abstract: Breast cancer (BC) is the second leading cause of cancer death among women worldwide. The main cause of BC morbidity and mortality is the invasiveness capacity of cancer cells that may lead to metastasis. Here, we aimed to investigate the therapeutic efficacy of Ganoderma lucidum extract (GLE)—a medicinal mushroom with anticancer properties—on BC motility via the Rac/Lamellipodin pathway. GLE treatment effects were tested on MDA-MB-231 breast cancer cells. The effects were tested on cell viability, migration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
(89 reference statements)
0
18
0
Order By: Relevance
“…The mixture was filtered, and the residue was air dried and collected before it was placed into a desiccator with concentrated H 2 SO 4 for three days to produce anhydrous [Co(phen) 2 (H 2 O) 2 ](NO 3 ) 3 3, which was then used in the subsequent syntheses. Yield = 2.44 g (65%) 1 Conductivity measurements (a 1.0 mM solution): In CH 3 CN, Λ m = 295 Ω −1 cm −1 mol −1 and in DMSO, Λ m = 72 Ω −1 cm −1 mol −1 .…”
Section: Synthesis Of the Ligand And [Co(phen) 2 (O 2 Co)]pf 6 -mentioning
confidence: 99%
See 2 more Smart Citations
“…The mixture was filtered, and the residue was air dried and collected before it was placed into a desiccator with concentrated H 2 SO 4 for three days to produce anhydrous [Co(phen) 2 (H 2 O) 2 ](NO 3 ) 3 3, which was then used in the subsequent syntheses. Yield = 2.44 g (65%) 1 Conductivity measurements (a 1.0 mM solution): In CH 3 CN, Λ m = 295 Ω −1 cm −1 mol −1 and in DMSO, Λ m = 72 Ω −1 cm −1 mol −1 .…”
Section: Synthesis Of the Ligand And [Co(phen) 2 (O 2 Co)]pf 6 -mentioning
confidence: 99%
“…The product's 1 H NMR spectrum was compared to the chemical shifts in the literature; where complex 3 was proven to be pure [155]. 1 H NMR spectra of complexes 2 and 3 are shown in Fig. S4, where the aromatic protons that were overlapping circa 7.5 ppm in complex 2 are no longer overlapping in complex 3.…”
Section: H 13 C and 59mentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer is the second major cause of death among cancers that are generally diagnosed in women [9,10]. Breast cancer commonly has invasive characteristics and a high rate of metastasis, which result in high morbidity and mortality [11,12]. Currently, chemotherapy, hormone therapy and targeted therapy are the most common breast cancer…”
Section: Introductionmentioning
confidence: 99%
“…G. lucidum is registered in the Chinese Pharmacopoeia for the efficacy of replenishing qi, tranquilizing the mind, and relieving cough and asthma ( Chinese Pharmacopoeia Commission, 2015 ). In the past few decades, it has been reported that G. lucidum has anti-cancer ( Li et al, 2013a ; Guo et al, 2018 ; Zhao et al, 2018 ; Zhu et al, 2018 ; Acevedo-Díaz et al, 2019 ), immunomodulatory ( Ishimoto et al, 2017 ), antioxidant ( Kan et al, 2015 ; Bhardwaj et al, 2016 ), antidiabetic ( Pan et al, 2013 ; Ma et al, 2015 ), antimicrobial ( Gaylan et al, 2018 ; Naveenkumar et al, 2018 ), hepatoprotective ( Chatterjee and Acharya, 2016 ), and anti-inflammatory ( Cai et al, 2016 ) effects. Since it has been proved to improve quality of life in cancer patients, G. lucidum preparation is widely used in adjuvant therapy for cancer as a traditional Chinese medicine ( Bao et al, 2012 ; Jin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%